Pengaruh Penggunaan Media Sosial Instagram Terhadap Pembentukan Citra Diri Mahasiswa Ilmu Komunikasi Universitas Singaperbangsa Karawang : Ilmu Komunikasi - Lutfiah, Cindy; Yuni Dharta, Firdaus; Oktariani Lubis, Fardiah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine how the duration and frequency of using Instagram social media influence the formation of self-image of communication science students at Singaperbangsa University, Karawang. The theory used is uses and effects by Sven Windahl. The method used is quantitative with probability sampling samples with simple random sampling techniques. The number of respondents used in this study was 187 respondents. The analysis used includes descriptive analysis, normality test, simple linear regression test, coefficient of determination, and t-hypothesis test. The results showed that the use of Instagram social media has a positive influence of 53.3% on the formation of self-image of communication science students at Singaperbangsa University, Karawang, while the remaining 46.5% is influenced by other factors.